Therapeutic target in patients with dementia†. Issue 2 (12th March 2012) - Priegue, M.; Pardo, C.; Hernandez, M.; Mas, P.
Abstract : Background: In order to reach reasonable therapeutic objectives among geriatric patients, the proper use of the Beers and STOPP-START criteria should be maximised. Purpose: To evaluate optimisation of the use of medicines in patients prescribed antidementia drugs. Materials and methods The study population included patients who had been diagnosed with dementia, which was defined as patients prescribed ATC N06D medicines. Outpatient pharmacological hospital profiles were reviewed at the time of admission to identify patients who might benefit from patient-centred interventions. Clinical judgement was used to detect potentially inappropriate prescriptions among these patients. Results: Over 1 year (2010), 93 individuals (average age 81.9±3.8 years) were evaluated and prescribed a mean of 8.7±3.7 medicines. Antidementia medicines were documented as follows: 33 (35%) patients were prescribed galantamine, 31 (32%) memantine, 16 (17%) rivastigmine and 15 (16%) donepezil. Eight patients were given memantine in addition to one of the others. In practice, patients with advanced disease are often prescribed additional medicines. In this study, 39 (42%) were prescribed neuroleptics, 45 (48%) antidepressants and 44 (47%) anxiolytics. All three classes were used in combination in 6 (6%) patients, and 17 (18%) were prescribed a two-drug combination of either anxiolytic/antidepressant or anxiolytic/neuroleptic. Four patients in our study were identified as candidates for changing the antidepressant treatment to drugs with a lower anticholinergic potential. Lipid-lowering medicines were prescribed in 32 (34%) patients. This class of drugs may not be warranted for patients diagnosed with dementia, as long-term benefit has not been fully demonstrated. Additionally, five patients were prescribed medicines from the N06BX nootropics and C04AE ergot alkaloids ATC classification; there is have little evidence to support the use of these drugs. Conclusions: By increasing access to therapeutic resources, providers can improve medicines selection and monitoring in patients with complex disease states. As this study demonstrates, future focus is warranted to improve the care of patients with dementia by identifying therapy optimisation strategies.